A Bibliometric Critique of Health Equity Research Growth in Nepal (2016-2025) - Shrestha, Hira Lal; Paudel, Binaya; Paudel, Suman; Gurung, Manoj; Khatiwada, Bipana (NPRC Journal of Multidisciplinary Research, 2025)
Background: Health equity remains a critical challenge in Nepal, a country with marked socioeconomic, ethnic, and geographic diversities. A better understanding of the research landscape is required for the identification of knowledge strengths and gaps, as well as collaborative pathways that inform policy and practice related to reducing health disparities.Objectives: This paper performs a bibliometric analysis that systematically maps and analyzes the scholarly literature on health access, equity, and disparities in Nepal during the period of 2016-2025, focusing on social determinants such as caste, ethnicity, and gender. It seeks to identify the trends of publication, dominant research themes, key contributing disciplines, and the structure of scientific collaboration networks.Methods: A systematic search was conducted on The Lens Scholarly database. The search statement used key terms for health equity ("health access", "health equity", "healthcare disparity") combined with social determinants ("caste", ethnicity, "social exclusion", gender). It was limited to journal articles about Nepal for the period of 2016-2025. Bibliometric analysis on the resultant dataset was conducted examining publication volumes, title keywords via word cloud, fields of study, and co-authorship networks.Findings: Mapping reveals a strong and increasing growth, especially post-2021. Dominant themes in the literature are health systems, maternal/child health, and mental health, but there is a strong and consistent focus on inequality, socioeconomic status, and rural/urban disparities. Discipline: Again, the research is interdisciplinary-led by Medicine and Public Health but strongly supported by Sociology, Economics, and Political Science. Co-authorship network: A clear pattern of co-author networks can be seen-a well-connected international cluster, led by figures like Thornicroft and Kohrt, working in collaboration with a tight national Nepali cluster, for example, Luitel, Lamichhane-with a number of bridging people.Conclusion: This is a lively, growing research area; biomedical and social science perspectives come together well. However, network structure does point to a possible dichotomy between globally and locally led research priorities. Future progress is attached with equitable partnerships, with the lead from local researchers on priority topics.Novelty: This review represents the first bibliometric mapping of the health equity research of Nepal, uniquely combining thematic, temporal, and disciplinary with social network analysis to reveal not only what is being studied but also how and by whom. This provides critical insight into the nature of the collaborative dynamics shaping the national research ecosystem in this field.